Pt-Sputtered Ti Mesh Electrode for Polymer Electrolyte Membrane Fuel Cells - Kang, Yun Sik; Jo, Sunhee; Choi, Daeil; Kim, Jin Young; Park, Taehyun; Yoo, Sung Jong (KOREAN SOC PRECISION ENG, 2019)
We suggest a new type of membrane-electrode assembly (MEA) for polymer electrolyte membrane fuel cells (PEMFCs) to substitute the conventional Pt/C catalyst layer and carbon-based gas diffusion layer. We fabricated the MEA by simply sputtering Pt on a commercially-available, porous Ti mesh, and this was directly hot-pressed into the polymer electrolyte membrane and thereby utilized as anodic and cathodic electrodes for PEMFC without any additional processing. The existence of Pt sputtered on the Ti mesh was confirmed via scanning electron microscopy with electron dispersive spectroscopy. In addition, the physical and electrochemical properties of Pt-sputtered Ti mesh were examined via X-ray diffraction and various electrochemical methods. The Pt-sputtered Ti mesh exhibited good catalytic activity toward hydrogen oxidation and oxygen reduction reactions, indicating that this Pt-sputtered Ti mesh can be applied as both electrodes for PEMFC. Finally, we also realized the fuel cell using a Pt-sputtered Ti mesh, and it showed a high open circuit voltage of 0.825V and peak power density of 3.37mW/cm(2), which confirms its potential applicability to a real PEMFC operating environment.